The Effect of Service Quality, Location, and Price on Repurchase Intention at J&T Express with Customer Satisfaction as a Mediation Variable - Wijaya, Renaldo; Pasaribu, Lamhot Henry (International Journal of Social Service and Research, 2024)
Technological advances and innovations that have occurred since 2000 have brought Indonesia's economic conditions to be all-digital and online. The emergence of business that is carried out online finally requires goods delivery services or logistics as a support to make it easier for business people to send goods to their buyers. This study aims to find out a company engaged in logistics that has been established since 2015. This study aims to determine the effect of Service Quality, Location, and Price on Repurchase Intention at J&T Express through mediation of Customer Satisfaction variables. This research was conducted using quantitative data collection method through google form, as many as 161 respondents have been obtained and analyzed using Smart-PLS. The results of this study show that Service Quality, Location, and Price have a positive effect on the dependent variable, namely Repurchase Intention and on the Customer Satisfaction mediation variable.